Regulatory T cells, interleukin (IL)‐6, IL‐8, Vascular endothelial growth factor (VEGF), CXCL10, CXCL11, epidermal growth factor (EGF) and hepatocyte growth factor (HGF) as surrogate markers of host immunity in patients with renal cell carcinoma. (15th March 2013) - Polimeno, Marianeve; Napolitano, Maria; Costantini, Susan; Portella, Luigi; Esposito, Arianna; Capone, Francesca; Guerriero, Eliana; Trotta, AnnaMaria; Zanotta, Serena; Pucci, Luigi; Longo, Nicola; Perdonà, Sisto; et al.
Abstract : Objective: To identify a phenotype that could be informative and prognostic in patients with renal cell carcinoma (RCC) peripheral blood was evaluated for TH1, TH2, regulatory T cells (Tregs), natural killer (NK) and NKT cells and for cytokines/chemokines. Patients and Methods: Peripheral blood from 77 patients with RCC and 40 healthy controls was evaluated by flow cytometry using monoclonal antibodies against CD4, CD25, FoxP3, CD45RA, CD45RO, CD152, CD184, CD279, CD3, CD16, CD56, CD161, CD158a, CD4, CD26, CD30, CD183 and CD184. A concomitant evaluation of 38 molecules was conducted in patients' serum using a multiplex biometric ELISA‐based immunoassay. Results: The number of NK cells CD3 − /CD16 +, CD3 − /CD16 + /CD161 + (NK) and CD3 − /CD16 + /CD161 + /CD158a + (NK‐ Kir 2+) was greater in the patients with RCC ( P < 0.05); and the number of Treg cells CD4 + /CD25 high + /FOXP3 + and the subset CD4 + /CD25 high + /FOXP3 + /CD45RA + (naïve) and CD45R0 + (memory) cells, were greater in the patients with RCC ( P < 0.001). An increase in the following was observed in the serum of patients with RCC compared with healthy controls: interleukin (IL)‐4, IL‐6, IL‐8, IL‐10, G‐CSF, CXCL10, CXCL11, hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF). According to Ingenuity Pathway Analysis (IPA), CXCL10, IL‐6, IL‐8, epidermal growth factor (EGF), HGF and VEGF were associated with a network that controls cellular movement, tissue development and cellular growth. Kaplan–Meier analysis for disease‐free survival showed that high numbers of CD4 + /CD25 high + /FOXP3 + /CD45RA + (Treg naïve) and low numbers of CD3 − /CD16 + /CD161 + /CD158a + (NK‐Kir+) cells predict short disease‐free survival in patients with RCC. Conclusion: Concomitant evaluation of Treg (CD4 + /CD25 high + /FOXP3 + and CD4 + /CD25 high + /FOXP3 + /CD45RA + ) and of six soluble factors (IL‐6, IL‐8, VEGF, CXCL10, CXCL11, EGF, HGF) might be a surrogate marker of host immunity in patients with RCC.